Vortex-induced Vibration of a Flexible Free-hanging Circular Cantilever - Prastianto, R. W.; Otsuka, K.; Ikeda, Y. (Journal of Engineering and Technological Sciences, 2009)
TheÂ  behaviorÂ  ofÂ  aÂ  free-hangingÂ  riserÂ  ofÂ  floatingÂ  offshoreÂ  structures would be different fromÂ  aÂ  typical at-sea-floor-terminated riser type of oil or gas platforms.Â  For the design purpose, the present studyÂ  was intended to incorporate someÂ  importantÂ  factorsÂ  of the riser conditionsÂ  (i.e.Â  bidirectional vibration,Â  freeend condition, and spanwise variation of response amplitude) for investigating its dynamicsÂ  characteristics.Â  AnÂ  experimentalÂ  investigationÂ  onÂ  time-dependent motionÂ  ofÂ  aÂ  flexible free-hanging circular cantileverÂ  subjected to uniform crossflows has been carried out.Â  TheÂ  free-end conditionÂ  cantilever hasÂ  aÂ  34.4Â  aspect ratioÂ  andÂ  aÂ  lowÂ  mass ratioÂ  ofÂ  aboutÂ  1.24. TheÂ  cylinderÂ  freelyÂ  oscillates in both inlineÂ  andÂ  transverseÂ  toÂ  theÂ  flow.Â  ReynoldsÂ  numberÂ  variedÂ  fromÂ  10,800Â  to 37,800.Â  The âjumpÂ  phenomenonâÂ  was found in the inline motionÂ  of the cylinder that agrees well with an existingÂ  comparable work.Â  At high flow velocities, the 3rdÂ  higherÂ  harmonicÂ  frequenciesÂ  ofÂ  theÂ  cylinderÂ  transverseÂ  responseÂ  became predominant that produce quite different motionÂ  characteristicsÂ  compared to the otherÂ  existingÂ  comparableÂ  worksÂ  withÂ  2-dimensionalÂ  bottom-endÂ  condition. Generally, the results suggested that the flexible free-hanging cantilever generate differentÂ  vortexÂ  wakeÂ  modeÂ  thanÂ  either,Â  aÂ  uniformÂ  (aÂ  short-rigidÂ  flexiblymounted cylinder) or a linear amplitude variation along the spanÂ  case (aÂ  pivoted cylinder)